2019
DOI: 10.1590/s0102-865020190080000005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sevoflurane pretreatment in relieving liver ischemia/reperfusion-induced pulmonary and hepatic injury

Abstract: Purpose To investigate the effect of sevoflurane preconditioning on ischemia/reperfusion (I/R)-induced pulmonary/hepatic injuryMethods Fifty-one Wistar rats were randomly grouped into sham, I/R, and sevoflurane groups. After reperfusion, the structural change of the lung was measured by Smith score, the wet and dry weights (W/D) were determined, malondialdehyde (MDA) myeloperoxidase (MPO) content was determined colorimetrically and by fluorescence, respectively, and matrix metalloprotein-9 (MMP-9) mRNA was qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Volatile anesthetics may decrease IRI-induced cytokine-mediated lung injury during thoracic procedures, in particular TNF- α , IL-1 β , IL-6, IL-8, and IL-10 [ 21 , 25 27 ]. Xu et al showed in a rat model that SEV preconditioning had a protective effect on IRI-induced pulmonary injury, by inhibiting leukocyte recruitment and MMP-9 secretion [ 17 ]. Ohsumi et al suggested that preconditioning or postconditioning of the lungs with SEV can display a protective effect against IRI injury in a rat LTx model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Volatile anesthetics may decrease IRI-induced cytokine-mediated lung injury during thoracic procedures, in particular TNF- α , IL-1 β , IL-6, IL-8, and IL-10 [ 21 , 25 27 ]. Xu et al showed in a rat model that SEV preconditioning had a protective effect on IRI-induced pulmonary injury, by inhibiting leukocyte recruitment and MMP-9 secretion [ 17 ]. Ohsumi et al suggested that preconditioning or postconditioning of the lungs with SEV can display a protective effect against IRI injury in a rat LTx model.…”
Section: Discussionmentioning
confidence: 99%
“…In LTx, preconditioning of lungs with inhaled SEV has been associated with reduced IRI injury in ex vivo models of isolated rat lungs [ 16 ], in an in vivo model of rat pulmonary and hepatic injury [ 17 ], and in an in vivo model of swine autotransplantation [ 18 ]. Kalb et al showed that preconditioning but not postconditioning with SEV has beneficial effects in a rat IRI model [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…member of the antioxidant metalloenzymes (Xu et al, 2019). MDA, SOD, and ROS are able to directly respond to oxidative stress (Abdel-Gaber et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…MDA is the most important metabolite of membrane lipid peroxidation, which can aggravate cell membrane damage and alter the activity of key enzymes in the mitochondria. Meanwhile, SOD is a vitally important member of the antioxidant metalloenzymes ( Xu et al., 2019 ). MDA, SOD, and ROS are able to directly respond to oxidative stress ( Abdel-Gaber et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation